Decision-Making Competence, Social Orientation, Time Style, and Perceived Stress - Geisler, Martin; Allwood, Carl Martin (Frontiers in Psychology, 2018)
Peoples’ decision-making competence, defined as tendency to follow normative rational principles in their decision making, is important as it may influence the extent that requirements are met and levels of perceived stress. In addition, perceived stress could be influenced by social and temporal aspects; for example, decisions need to comply with given deadlines and the expectations of others. In two studies, with students (n = 118) and professionals (police investigators, n = 90), we examined how the three individual difference features: decision-making competence, social orientation, and time approach relate to perceived stress. Results showed that social orientation and time approach were related to levels of perceived stress, but decision-making competence was not. These results indicate that social orientation and time approach are important to consider in relation to perceived stress, but the role of decision-making competence may be less important for perceived stress. However the role of decision-making competence for perceived stress needs to be further researched.